2004
DOI: 10.1007/s00296-004-0472-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary involvement in rheumatoid arthritis

Abstract: The primary objective of this investigation was to assess the relationships between clinical characteristics, lung involvement, and frequency of pulmonary involvement in rheumatoid arthritis (RA). Using high-resolution computed tomography (HRCT) and pulmonary function tests (PFT), we prospectively evaluated 52 patients with RA (eight males and 44 females, mean age 53.6 years). The HRCT was abnormal in 35 patients (67.3%), the most frequent abnormalities being reticulonodular patterns, which were found in 22 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
4
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 24 publications
8
100
4
9
Order By: Relevance
“…The analysis of the data of the present study shows that most patients with RA (55%) have some type of CT changes. That high prevalence of fi ndings has been confi rmed by other authors, such as Zrour et al, 11 who have reported changes in 49.3% of 75 patients from Tunisia, and Bilgicki et al, 3 who have reported them in 67.3% of 52 patients in Turkey. In addition, Teraski et al, 12 studying patients with RA and respiratory symptoms, have reported CT changes in 90% of them.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The analysis of the data of the present study shows that most patients with RA (55%) have some type of CT changes. That high prevalence of fi ndings has been confi rmed by other authors, such as Zrour et al, 11 who have reported changes in 49.3% of 75 patients from Tunisia, and Bilgicki et al, 3 who have reported them in 67.3% of 52 patients in Turkey. In addition, Teraski et al, 12 studying patients with RA and respiratory symptoms, have reported CT changes in 90% of them.…”
Section: Discussionsupporting
confidence: 56%
“…Tobacco, a potentially harmful agent to the lungs, is also an aggravating factor of RA, causing not only a more aggressive disease, but also the appearance of more extra-articular manifestations. 3 The present study aimed at assessing the tomographic fi ndings of RA patients of a single rheumatology center in southern Brazil, and their possible correlation with the clinical and serological fi ndings of the disease.…”
Section: Rev Bras Reumatol 2011;51(4):325-37mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of cases of RA-ILD occur in patients between the ages of 50 and 60 years. While several studies 13,[15][16][17]20 have reported smoking, male gender, and longstanding RA to be risk factors for the development of ILD, other reports 13,14,16,17,19 have not shown any significant associations. In addition, genetic associations (human leukocyte antigen B40 and ␣ 1 -antitrypsin) have been described.…”
Section: Ra-ild: Epidemiology and Clinical Presentationmentioning
confidence: 86%
“…Studies [12][13][14][15][16][17][18][19] have reported a prevalence as low as 4% and as high as 68%. The majority of cases of RA-ILD occur in patients between the ages of 50 and 60 years.…”
Section: Ra-ild: Epidemiology and Clinical Presentationmentioning
confidence: 99%